Incidencia de las técnicas grafo plásticas para el desarrollo de la creatividad en los niños y niñas de educación inicial y primer año de los centros de educación general básica rotary club Machala moderno y Andrés Cedillo prieto, de la ciudad de Machala, período lectivo 2012-2013. - Ruiz Agila, María Isabel (2015)
Graph expression of Technical Plastic, occur through creativity, as children are motivated to streamline their creativity is manifest that the student and also learn during the teaching-learning process enabling the materialization of ideas along with the formation and development of the motor itself, affect and cognition of the child. This research has an educational value as creativity appears as a fundamental aspect of human beings. We considered that the Technical Plastic Graph are an extremely valuable discipline in the education. A kindergarten teacher who encourages creativity positively affect children. Children should not be deprived of basing their creativity, as art develop better skills and abilities to deal with problems and situations that arise, which means a better development of thought, imagination, socialization and creativity. Plenty to do and an overwhelming way to go to achieve the ultimate recognition of Grafo art techniques, as an essential area ofstudent training.